Poems from GeoPoetics Session: True or False, Appendix: Wild Hyacinth, Underbrush. Issue 1 (2nd January 2017) - Halebsky, Judith
Abstract : These poems are from the GeoPoetics Poetry Reading at the American Association of Geographers conference in March 2016. The session was sponsored by the Cultural Geography Specialty Group and organized by Sarah De Leeuw and Tim Cresswell.